A Rapid Transition from Campus to Emergent Distant Education; Effects on Students' Study Strategies in Higher Education - Lena Boström; Charlotta Collén; Ulla Damber; Ulrika Gidlund (MDPI AG, 2021)
This article presents a literature review focusing on international research concerning distance education and students' study strategies during the last 20 years. As distance education in higher education is a steadily growing trend and in particular because the COVID-19 pandemic has escalated the transition from campus education to different forms of distance education, knowledge about students' study strategies and appropriate teaching strategies has become highly important. With this research review, we aimed to identify patterns and trends in research on distance education focusing students study strategies before and after the pandemic. The research synthesis identified and interpreted similarities and differences in the studies' designs and findings, which we analyzed using integrative thematic analysis. Students' study strategies seem to have changed to some extent during the pandemic, with more emphasis on their own responsibility and the need for a developed teaching strategy to align with the changing framework related to the emergency provision of distance education. We concluded that students have to develop metacognitive strategies, because self-regulated learning and a more flexible pedagogy seem to be important in teachers' transitions and competence in digitalization. Therefore, more research targeting these aspects is needed.